Association of Prenatal Famine Exposure With Inflammatory Markers and Its Impact on Adulthood Liver Function Across Consecutive Generations - Yan, Shiwei; Ruan, Jingqi; Wang, Yu; Xu, Jiaxu; Sun, Changhao; Niu, Yucun (Frontiers in Nutrition, 2022)
Although there has been increasing recognition that famine exposure in the fetal stage damages liver function in adulthood, this deteriorated effect could be extended to the next generation remains vague. This study aimed to explore whether famine exposure was associated with liver function in the two consecutive generations, and its association with the mediation role of inflammatory markers. We analyzed the data of 2,681 participants from Suihua rural area, Heilongjiang Province, China. According to the date of birth, the participants were classified as fetal exposed and nonexposed. The F2 subjects were classified as having no parents exposed to famine, maternal famine exposure, paternal famine exposure, or parental famine exposure. In the mixed-effect models, prenatal exposure to famine was associated with the elevation of Δ aspartate aminotransferase (ΔAST) (β: 0.22, 95% CI: 0.01, 0.43) and Δ alanine aminotransferase (ΔALT) (β: 0.42, 95% CI: 0.19, 0.66) levels in F1 adults. The mediation analysis showed that the inflammatory markers including serum C-reactive protein (CRP) and tumor necrosis factor-alpha (TNF-α) might mediate the famine-liver function association. This longitudinal data were consistent with the hypothesis that the inflammatory markers explained part of the influence of prenatal famine exposure on liver function injury, and the natal mechanism was needed to be elucidated in the future study.